Parallel Bioinformatics Algorithms for CUDA-Enabled GPUs (Bioinformatics, 2011)
Bioinformatics has evolved into a compute-intensive and data-intensive research area driven by advances in both computer hardware and software algorithms. Therefore, many important biological problems are facing challenges both in runtime and memory consumption because of the exponential growth of biological databases. Problem examples include sequence alignments and motif discovery.